Conjoined Twin Marriages in the Perspective of Islamic Law - Ma’adul Yaqien Makkarateng; Muljan; Nurfajriani (Jurnal Hukum Islam, 2023)
Conjoined twins have rights that must be fulfilled like other humans, namely the right to marry. However, Islamic Law scholars still debate the validity of conjoined twin marriages. This research discusses the debate about the marriage of conjoined twins in Islamic law. The research method uses normative juridical with an Islamic legal approach. The results show that conjoined twins are generally divided into two groups, conjoined twins who can be separated by surgery and conjoined twins who cannot be separated by surgery. Based on the organs or body parts that are connected or united, conjoined twins are divided into several types, such as cephalopagus, thoracopagus, omphalopagus, ischiopagus, craniopagus, heteropagus, epigastric heteropagus, phygopagus, thoraco-omphalopagus, prosopo-thoracopagus, rachipagus, parapagus and dicephalic parapagus. Islamic law does not specifically explain the type of marriage of conjoined twins. However, the law of conjoined twin marriage can be determined by classifying whether each conjoined twin has the consciousness of one person or two people. Besides that, it can also be determined by organising it into one person from below the navel and two people united to form two bodies above. The legal determination of twins on different bases means that the validity of conjoined twin marriages is still debated in Islamic law.